Godzila - Sanjeev Srivatsan; Mekhala Venkatesh (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
Godzilla, the most iconic movie monster that everyone will think of whenever someone talk with people about a giant monster obliterating a city. Its legacy has been living for almost seventy years and will keep live for the years to come. From looking at the perspective of Ecocentric theory, it seems that Godzilla is a force of nature that obliterates the Japanese city Tokyo to teach humans a lesson that our selfishness, arrogance and the attitude of placing ourselves on top of nature would only lead to tragic consequences. Using Conceptual Metaphor Theory, this article discuss about the movies which actually focuses on the core element of Godzilla instead of the portrayal of Godzilla as a monster fighter or as a savior of humanity in the aspects of ecocriticism, environmentalism, politics and post-modernism, along with the king of the monsters.